Maize breeding in East and Southern Africa, 1900-2000 - Smale, Melinda; Jayne, Thomas S. (International Food Policy Research Institute, 2004)
During the first half of the 20th century, African farmers transformed maize from a minor imported foodcrop into the continent's principal staple food. In the second half of the century, newly independent governments launched support programs that greatly expanded smallholder production, leading to substantial production surges of 10 to 20 years in duration. Today, after widespread adoption by both commercial farmers and smallholders, farmers now plant 58 percent of all maize area in East and Southern Africa to new high-yielding varieties, which on average outyield traditional varieties by 40-50 percent even without fertilizer....Though these maize-breeding efforts were an undeniable technical success, broader efforts to support national production growth proved fiscally unsustainable, and once heavy subsidies were withdrawn, production fell (see table). This qualified success story reveals important lessons about both the strengths and pitfalls of past agricultural development efforts in Africa.